Analisis Peran Ekonomi Kreatif Dalam Peningkatan Pendapatan Pengrajin Ditinjau Dari Ekonomi Islam (Studi Pada Industri Bordir Kecamatan Indrajaya Kabupaten Pidie) - Murni, Seri; R, Rekha (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2021)
This study aims to reveal the role of the creative economy in increasing the income of embroidery craftsmen in Indrajaya District, Pidie Regency. This thesis uses a descriptive qualitative approach with data collection methods through observation, interviews and documentation. The results of the study illustrate that the creative economy of the embroidery industry in Indrajaya sub-district, Pidie Regency is already good, it can be seen from 15 craftsmen found that 9 craftsmen experienced an increase in income, 6 craftsmen with stable income from 2019 to 2020. While in the Islamic economic perspective, the craftsmen have fulfilled the production process , marketing markets, government policies, economic conditions and partnerships, but have not met the management and financial indicators.